2020
DOI: 10.1186/s12904-020-00586-1
|View full text |Cite|
|
Sign up to set email alerts
|

Content validation of the EORTC QLQ-C15-PAL with advanced cancer patients and health care professionals from palliative care services in Chile

Abstract: Background The assessment of patients’ quality of life (QOL) is essential when evaluating the outcome of palliative care; however, no instruments have been validated for measuring symptoms and QOL in patients receiving palliative care in Chile. We aimed to investigate the content validity of the EORTC Quality of Life Questionnaire Core 15 Palliative Care (QLQ-C15-PAL), replicating the methods used previously to shorten the EORTC Quality of Life Questionnaire Core 30 (QLQ-C30) for use among patients in palliati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…La validación del EORTC QLQ-C15-PAL para Colombia demostró propiedades psicométricas satisfactorias al aplicarse en pacientes con enfermedad oncológica avanzada; estos hallazgos son similares a los encontrados en un estudio realizado en Chile (20) . La correlación inter-escalas demuestra que el EORT QLQ 15 PAL presenta consistencia entre las escalas que lo componen.…”
Section: Discussionunclassified
“…La validación del EORTC QLQ-C15-PAL para Colombia demostró propiedades psicométricas satisfactorias al aplicarse en pacientes con enfermedad oncológica avanzada; estos hallazgos son similares a los encontrados en un estudio realizado en Chile (20) . La correlación inter-escalas demuestra que el EORT QLQ 15 PAL presenta consistencia entre las escalas que lo componen.…”
Section: Discussionunclassified
“…European Organisation for Research and Treatment of Cancer Quality of Life 15‐item Questionnaire for Palliative Care was the second instrument included in the largest number of studies, 14 in total (Alawneh et al, 2016; Arraras et al, 2014; Golčić et al, 2018; Groenvold et al, 2006; Leppert & Majkowicz, 2013; Miyashita et al, 2015; Miyazaki et al, 2012; Nunes, 2014; Ozcelik et al, 2016; Raman et al, 2016; Rojas‐Concha et al, 2020; Shin et al, 2011; Suárez‐del‐Real et al, 2011; Zhang et al, 2016) and for which more psychometric properties were measured: content validity, structural validity, internal consistency, cross‐cultural validity, reliability, criterion validity, hypotheses testing and responsiveness (all except for measurement error). The content validity was classified as ‘inadequate’ for the two studies where it was evaluated (Groenvold et al, 2006; Rojas‐Concha et al, 2020). Structural validity was rated as ‘adequate’ or ‘very good’ and was present in three of the studies (Alawneh et al, 2016; Miyashita et al, 2015; Nunes, 2014).…”
Section: Psychometric Propertiesmentioning
confidence: 99%
“…The structural validity was 'inadequate'. As a result, an exploratory factorial analysis was carried out, and three factors were identified by means of the Scree test: 'physical subscale' (the first subscale consisted of seven items that were related to the physical sensations of fatigue; easily tired, having urge to lie down, exhausted, heavy and tired, fed-up, reluctant and fatigue you do not know what to do with yourself), 'affective subscale' (the second subscale consisted of four items that assessed affective activity; energetic feeling, interest in something, ability to concentrate and encourage yourself to do something) and 'cognitive subscale' (the third subscale consisted of four items that assessed attention and memory; careless, instrument included in the largest number of studies, 14 in total (Alawneh et al, 2016;Arraras et al, 2014;Golči c et al, 2018;Groenvold et al, 2006;Leppert & Majkowicz, 2013;Miyashita et al, 2015;Miyazaki et al, 2012;Nunes, 2014;Ozcelik et al, 2016;Raman et al, 2016;Rojas-Concha et al, 2020;Shin et al, 2011;Suárez-del-Real et al, 2011;Zhang et al, 2016) and for which more psychometric properties were measured: content validity, structural validity, internal consistency, cross-cultural validity, reliability, criterion validity, hypotheses testing and responsiveness (all except for measurement error). The content validity was classified as 'inadequate'…”
Section: Cancer Fatigue Scalementioning
confidence: 99%
See 1 more Smart Citation
“…Following publication of the original article [ 1 ], the authors identified an error in Table 3 . The footnotes were missing.…”
mentioning
confidence: 99%